2019
DOI: 10.1177/0361198119846481
|View full text |Cite
|
Sign up to set email alerts
|

Familiar versus Unfamiliar Drivers on Curves: Naturalistic Data Study

Abstract: Human factors studies have shown that route familiarity affects driver behavior in various ways. Specifically, when drivers become more familiar with a roadway, they pay less attention to signs, adopt higher speeds, cut curves more noticeably, and exhibit slower reaction times to stimuli in their peripheral vision. Numerous curve speed models have been developed for purposes such as predicting driver behavior, evaluating roadway design consistency, and setting curve advisory speeds. These models are typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Moreover, recent studies have explored driver behaviour at horizontal curves using the Naturalistic Driving Study (NDS) and the results concluded that the importance of speed behaviour as well as driver comfortable thresholds while traversing horizontal curves needs to be considered to maintain design consistency (Dhahir and Hassan, 2018). Whereas, in another NDS research, has shown that the driver's familiarity with the curves and the results identified that driver familiarity has a significant role in choosing higher vehicle speeds along the curves (Pratt et al, 2019). Further, in some of the studies, familiarity and unfamiliarity were considered accident factors (Intini et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, recent studies have explored driver behaviour at horizontal curves using the Naturalistic Driving Study (NDS) and the results concluded that the importance of speed behaviour as well as driver comfortable thresholds while traversing horizontal curves needs to be considered to maintain design consistency (Dhahir and Hassan, 2018). Whereas, in another NDS research, has shown that the driver's familiarity with the curves and the results identified that driver familiarity has a significant role in choosing higher vehicle speeds along the curves (Pratt et al, 2019). Further, in some of the studies, familiarity and unfamiliarity were considered accident factors (Intini et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%